The Mosque Welfare Agency’s Strategy in Developing the Leadership of Muslim Youth in Sorong City - Hasbullah; Sunatar, Bambang; Yusof, Sanitah Bte. Mohd. (Al-Ishlah: Jurnal Pendidikan Islam, 2025)
Background: The Nurul Bahri’s Mosque Welfare Agency (BKM) develops local wisdom leadership in fostering the skills and harmony of the Muslim young generation. Research Objective: This study aims to explore the strategies in fostering Islamic leadership among youth at the Nurul Bahri Mosque in Sorong City, Southwest Papua Province, Indonesia, and its contribution to maintaining a harmonious life. Methods: This qualitative study used interviews, observation, and documentation with six BKM administrators, three mosque youth mentors, and ten purposively selected active youths engaged in leadership, arts, culture, organizational activities, and community development within mosque-based programs. This study collected data over a period of about ten months, from June 2024 to April 2025. Results: The results show that the youth development has advanced from informal activities to structured programs that enhance confidence, leadership, communication, and cultural skills. Islamic arts serve as both a means of religious outreach and a medium for creativity, social legitimacy, and interfaith tolerance. These outcomes differ from Lombok’s predominantly Muslim yet ethnically rooted Sasak culture, Belgium’s highly diverse and secular European population, and Malaysia’s multicultural Malay–Chinese–Indian society. Each demographic context shapes youth engagement and cultural expression differently, making this mosque-based model distinctive. Conclusion: This study concludes that BKM Nurul Bahri Mosque develops an integrative youth model blending spiritual education, skills training, and Islamic arts, recommending mosque adoption and policy support to strengthen youth leadership, cultural engagement, and social harmony in multicultural communities.